Sosialisasi dan Pelatihan Teknologi Tatakelola Perkuliahan Berbasis Smart Things - Elyas Palantei; Andani Achmad; Syafruddin Syarif; Azran Budi Arief; Ida Rachmaniar; Zulfajri Basri Hasanuddin; Samuel Panggalo; Tajuddin Waris; Andini Dani Achmad; Merna Baharuddin; Idris Palantei (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2024)
This community service activity is a form of implementation of the results of research and innovation in the Department of Electrical Engineering related to the development of smart things-based lecture technology. The technology disseminated in this activity includes hardware, software and work procedures to support campus operations towards an intelligent system. It is hoped that the aim of this activity will be to develop similar technology by the Muhammadiyah University (Unismuh) Bone campus as a partner in this activity. This Community Service (PkM) activity program is a structured and sustainable effort that can be implemented by partners to increase efficiency in lecture management, reduce routine workload, and improve student learning experiences. Many infrastructure and strategic objects on the Unismuh Bone campus have the potential to be connected to the internet network so that governance arrangements are easier, more effective and optimal. This PkM program is designed to introduce and integrate advanced technology such as the Internet of Things (IoT), sensors, data analysis and automation into lecture management which currently relies on manual processes. Lecturers, administrative staff and students at partner universities have been involved in various integrated activities such as workshops/seminars, tutorials and demonstrations/practical training aimed at providing the understanding and skills needed to adopt technology. With the help of digital technology, partners are expected to be able to further optimize class management, evaluation, attendance monitoring, and utilization of physical and digital resources. To evaluate the success of the activity, a questionnaire was administered before (pre-test) and after (post-test) the activity. The evaluation results show that there is an increase in partner understanding related to smart things-based governance technology.